2021
DOI: 10.3390/microorganisms9102038
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis Determines the Functional Genes Related to Bile Salt Resistance in Lactobacillus salivarius

Abstract: Lactobacillus salivarius has drawn attention because of its promising probiotic functions. Tolerance to the gastrointestinal tract condition is crucial for orally administrated probiotics to exert their functions. However, previous studies of L. salivarius have only focused on the bile salt resistance of particular strains, without uncovering the common molecular mechanisms of this species. Therefore, in this study, we expanded our research to 90 L. salivarius strains to explore their common functional genes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…We have previously reported that L. salivarius improved the growth and health of weanling piglets [ 7 ]. Genomic evaluation was first used to obtain the genetic information of L. salivarius [ 18 , 31 ]. The phylogenetic tree suggested that L. salivarius was closely related to Ligilactobacillus salivarius MT57355.1 and MT585431.1, probiotic bacteria isolated from animals.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that L. salivarius improved the growth and health of weanling piglets [ 7 ]. Genomic evaluation was first used to obtain the genetic information of L. salivarius [ 18 , 31 ]. The phylogenetic tree suggested that L. salivarius was closely related to Ligilactobacillus salivarius MT57355.1 and MT585431.1, probiotic bacteria isolated from animals.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to tolerate bile salts is commonly known due to bile salt hydrolase activities ( Noriega et al, 2006 ). However, Pan et al (2021) have described the fact that, for some L. salivarius strains, other mechanisms could be responsible for this property. The growth of our strain was impacted by the low pH (pH 4 and pH 2) that mimic the passage in the gastrointestinal tract and, more specifically, gastric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, Fang et al demonstrated that BSH is not the primary determinant of bile resistance in L. salivarius strains, and may have additional biological importance because of its varying effects upon bile as a signaling molecule in the host [ 48 ]. Pan et al also showed that there was no association between bile salt hydrolase and bile salt tolerance in L. salivarius strains and indicated that bile salt tolerance in L. salivarius strains was associated with processes such as peptidoglycan synthesis, the phosphotransferase system (PTS) and DNA damage repair [ 49 ]. This is consistent with the results of Wang et al [ 50 ] and Lv et al [ 51 ].…”
Section: Probiotic Properties and Roles Of Ligilactobacillu...mentioning
confidence: 99%